Waveform Reconstruction of Lightning Current Based on Output‐Error Model and Finite‐Difference Time‐Domain Method. Issue 2 (2nd February 2021) - Fu, Yapeng; Zhang, Qi; Yang, Bo
Abstract: A simple method combining Output‐Error (OE) model and Finite‐Difference Time‐Domain (FDTD) method is proposed to reconstruct lightning current in this paper. First, the FDTD method is adopted to calculate electromagnetic fields of any desired point, and the transfer function between the obtained fields and channel base current is built by using OE model. Then, the lightning current is reconstructed by putting the actual measured electromagnetic field into the corresponding transfer function. The validity of the proposed method is demonstrated through the measured data given in the literature. Moreover, three influence factors on the reconstruction performance of this method are analyzed as well, including the effect of distance from field observation point to lightning channel, ground conductivity and the velocity of return stroke. Key Points: A simple method combining Output‐Error model and Finite‐Difference Time‐Domain method is proposed to reconstruct lightning current in this paper The validity of the proposed method is demonstrated through the measured data given in the literature The return stroke speed plays an important role in the reconstruction method